EUROPEAN FINANCIAL NETWORK OF ISLAMIST TERRORISM - Vukoičić, Jelena (Politeia, 2019)
In this paper the author analyses one of the most important aspects of global Islamist terrorism on the territory of Europe – the terrorism financing network. Although Europe has become on of the main targets of Islamist terrorists in recent years, its answer to the rising terrorism threat has, to this day, proven to be mild and ineffective. The same can be said regarding the European security officials’ fight against the financial networks of terrorist organisations. While the US, after the attacks on New York and Washington in 2001, established the “Patriot Act”, Europe did not follow through, which made it a perfect location for terrorists who were forced to withdraw their funds from America. The absence of a global and homogenous legislation comparable to the American “Patriot Act” can be partially explained by the fact that Europe does not possess the equivalent of a federal legislation because the degree of the political integration of the European Union members is much weaker than that of the American states. The lack of homogeneity of the European structures has allowed members of terrorist organisations to take advantage of gaps that exist in the local legislation of every country. Apart from the fact that the EU does not have a common set of anti-terrorism laws, its problem also lays in the fact that liberal-democratic European political elites place too much emphasis on the notion of human rights, which is, in fact, crippling their security forces and making it very hard for them to properly investigate individuals and organisations suspected of financing terrorist activities.
Keywords: Islamist terrorism; Islamist terrorist organisations; terrorism financing; Europe; EU; US